2021
DOI: 10.4143/crt.2020.275
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Variability in Dental Age Observed among Childhood Survivors Is Cancer Specific

Abstract: Purpose The study aimed to assess the differences in dental maturation between childhood cancer survivors and healthy children. Materials and Methods Fifty-nine cancer patients including 16 (27.1%) girls and 43 (72.8%) boys, aged between 4 and 16 years, underwent dental and radiographic examinations. The mean duration of anticancer therapy was 16.8 months (range, 1 to 47 months), and 4.6 years (range, 8 to 123 months) had passed since the termination of disease. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Previously, it was also found that cancer not only affects tooth development but also disturbs the process of dental maturity [ 14 ]. In most cases, cancer therapy may accelerate dental age; however, it was found to be delayed in patients suffering from (FAP)-associated hepatoblastoma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was also found that cancer not only affects tooth development but also disturbs the process of dental maturity [ 14 ]. In most cases, cancer therapy may accelerate dental age; however, it was found to be delayed in patients suffering from (FAP)-associated hepatoblastoma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was also found that cancer not only affects tooth development but also disturbs the process of dental maturity [ 14 ]. In most cases, cancer therapy may accelerate dental age; however, it was found to be delayed in patients suffering from (FAP)-associated hepatoblastoma [ 14 ]. Celikoglu et al found that orthodontic patients with skeletal malocclusions demonstrated approximately twice the mean difference between dental and chronological time than patients with Class I [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are summarised in Table 3. From the studies included into the analysis, six were cross-sectional (Shum et al 2020;Proc et al 2016;Flores et al 2015;Cubukçu and Sevinir 2008;Lopes et al 2006;Marec-Berard et al 2005), ten case-control studies (Mitsea et al 2022;Proc et al 2021;Kılınç et al 2019;Olczak-Kowalczyk et al 2018;Bagattoni et al 2014;Nemeth et al 2013Nemeth et al , 2014Cubukcu et al 2012;Oğuz et al 2004;Näsman et al 1994) and one cohort study (Shayani et al 2022). They were all published in English from 1994 until 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Essas drogas não se restringem apenas às células tumorais, mas sim a todas as células em multiplicação, provocando efeitos colaterais agudos como mucosite oral, alopecia, neutropenia e infecções oportunistas (Figliolia et al, 2008;Muniz et al, 2021). Pacientes pediátricos além dos efeitos agudos, também estão sujeitos a desenvolverem alterações tardias em estruturas que estiverem em formação (Günen Yılmaz et al, 2018;Proc et al, 2021). Uma recente revisão de literatura incluiu artigos publicados que relataram os principais efeitos agudos e tardios do tratamento oncológico.…”
Section: Introductionunclassified